2016
DOI: 10.1080/21645515.2017.1264798
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hepatitis A vaccination as post-exposure prophylaxis

Abstract: Hepatitis A (HA) has been a vaccine-preventable disease since 1995. In Catalonia, a universal combined hepatitis ACB vaccination program of preadolescents was initiated at the end of 1998. However, outbreaks are reported each year and post-exposure prophylaxis (PEP) with hepatitis A virus (HAV) vaccine or immunoglobulin (IG) is recommended to avoid cases.The aim of this study was to assess the effectiveness of HAV vaccine and IG in preventing hepatitis A cases in susceptible exposed people.A retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…183 Several reports confirmed the effectiveness of PEP using an inactivated HAV vaccine. 173,[184][185][186][187] Although controlled clinical trials have not been published in subjects aged 41 years and older, clinical experience from previous trials suggest that such a policy will also be effective in individuals older than 40 years old. 188 PEP through active vaccination is restricted to formalin-inactivated vaccines and should not be used with live attenuated vaccines.…”
Section: Active Immunisation With Hepatitis a Vaccinesmentioning
confidence: 99%
“…183 Several reports confirmed the effectiveness of PEP using an inactivated HAV vaccine. 173,[184][185][186][187] Although controlled clinical trials have not been published in subjects aged 41 years and older, clinical experience from previous trials suggest that such a policy will also be effective in individuals older than 40 years old. 188 PEP through active vaccination is restricted to formalin-inactivated vaccines and should not be used with live attenuated vaccines.…”
Section: Active Immunisation With Hepatitis a Vaccinesmentioning
confidence: 99%
“…The effectiveness of HAV vaccination in the outbreak setting has rarely been evaluated in high‐risk populations before. In a retrospective study focusing on post‐exposure prophylaxis for individuals who had exposure to index HAV cases during an outbreak, Parron et al . found that HAV vaccination resulted in a 97.6% reduction of secondary cases.…”
Section: Discussionmentioning
confidence: 99%
“…HAV vaccines, with or without HAV immune globulin, are also recommended by international guidelines for post‐exposure prophylaxis . Recently, Parron et al . reported using HAV vaccination as post‐exposure prophylaxis during outbreaks for patients exposed to index cases of acute hepatitis A, with an estimated efficacy of 97.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Such Taiwanese experience is paradigmatic of the central role that vaccination holds in the current epidemic control and further outbreaks prevention. Additionally, HAV vaccination as post‐exposure prophylaxis was found to protect with high efficacy (97.6%) in exposed individuals and comparable to anti‐HAV immunoglobulins …”
Section: Demographic and Clinical Features From Published Reports Of mentioning
confidence: 95%